1996
DOI: 10.1007/bf00019016
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an auxin-inducible glutathione S-transferase gene of Arabidopsis thaliana

Abstract: Genes homologous to the auxin-inducible Ntl03 glutathione S-transferase (GST) gene of tobacco, were isolated from a genomic library of Arabidopsis thaliana. We isolated a 2 clone containing an auxininducible gene, AtlO3-1a, and part of a constitutively expressed gene, AtlO3-1b. The coding regions of the Arabidopsis genes were highly homologous to each other and to the coding region of the tobacco gene but distinct from the GST genes that have been isolated from arabidopsis thusfar. Overexpression of a cDNA clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…In Arabidopsis, the safener dichlormid was only effective in inducing gstl1, suggesting that this safener, which is used to increase tolerance to chloroacetanilide herbicides in maize by enhancing the expression of multiple Phi and Tau GSTs (45), was far less active as a safener in Arabidopsis. The induction of gstl1 was not seen with the GST substrates CDNB and fluorodifen; instead these compounds were most effective in inducing the Tau GST gstu1, a gene shown previously (46) to be regulated by auxin. This result suggested that GST induction by safeners and xenobiotic substrates of GSTs must proceed by distinct recognition/signaling pathways.…”
Section: Discussionmentioning
confidence: 63%
“…In Arabidopsis, the safener dichlormid was only effective in inducing gstl1, suggesting that this safener, which is used to increase tolerance to chloroacetanilide herbicides in maize by enhancing the expression of multiple Phi and Tau GSTs (45), was far less active as a safener in Arabidopsis. The induction of gstl1 was not seen with the GST substrates CDNB and fluorodifen; instead these compounds were most effective in inducing the Tau GST gstu1, a gene shown previously (46) to be regulated by auxin. This result suggested that GST induction by safeners and xenobiotic substrates of GSTs must proceed by distinct recognition/signaling pathways.…”
Section: Discussionmentioning
confidence: 63%
“…The AtGSTU19 protein has significant similarity with other Arabidopsis tau class GSTs encoded by genes located outside the cluster on chromosome one (Table III), notably AtGSTU5 (GenBank accession no. D44465), which has been characterized previously (Van der Kop et al, 1996). AtGSTU19 is also very similar to members of the maize tau class of safener-inducible GSTs, ZmGSTU1 and ZmGSTU2 Figure 1.…”
Section: Table II Effect Of Safeners On Total Glutathione Content Inmentioning
confidence: 66%
“…Exposure to H 2 O 2 , diamide, 2,4-D, salicylic acid, and methyl viologen did not increase the levels of gsh1, gsh2, or gr1 mRNA, as shown in Figure 3. They did, however, increase the level of mRNA for a GST, parA, which is known to be activated by multiple stimuli (van der Kop et al, 1996). JA, unlike the other compounds tested, increased the level of all three mRNAs involved in GSH metabolism.…”
Section: Coordinated Expression Of Gsh Metabolic Genes In Response To Jamentioning
confidence: 78%